Study of pyrolysis kinetics of coal fines using model free method. (2022) - Prabhakar, Ashok; Kumar Sadhukhan, Anup; Gupta, Parthapratim
Abstract: The study is focussed on the experimental investigation of fine coal pyrolysis in TGA reactor. The non-isothermal pyrolysis experiment is conducted at three different heating rates (20, 30 and 40 °C/min) in Nitrogen ambience. The highest experimental temperature was maintained at 950 °C. The mass loss profile shows that higher heating rate favours the higher conversion as compared to low heating rate but the final conversion on the given time span is lower in the case of higher heating rate. The reaction kinetics is estimated using Iso-conversional method. activation energy varies from the range of 31.41 kJ/mol to 50.42 kJ/mol. Also, the pre-exponential factor value varies in the range of 1.05 × 10 6 to 1.4 × 10 7  min −1 . The average pre-exponential factor was calculated from the average energy of activation found by model-free method. The value of pre-exponential factor is found to be A0  = 5.52 × 10 10  min −1 .